Before Memory Fades : Emergence of Pakistan as A Nuclear Power - Abdul Waheed, Mian (Lahore Jumhoori Publications, 2013)
English Autobiography.
Include Illustrations.
Emergence of Pakistan as A Nuclear Power.
Keywords: Politicians -- Pakistan -- Politics and government -- Ambassadors